2016
DOI: 10.1186/s12864-016-2705-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of the sulfate transporter gene GmSULTR1;2b in soybean

Abstract: BackgroundSoybean is a major source of oil and protein in the human diet and in animal feed. However, as soybean is deficient in sulfur-containing amino acids, its nutritional value is limited. Increasing sulfate assimilation and utilization efficiency is a valuable approach to augment the concentration of sulfur-containing amino acids in soybean seeds, and sulfate transporters play important roles in both sulfate uptake and translocation within plants.ResultsIn this study, we isolated and characterized a soyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 70 publications
2
16
0
Order By: Relevance
“…To further investigate potential roles for soybean NRAMP genes in nutrient homeostasis, GmNRAMPs were tested for alterations in expression in response to Fe or S deficiency. Two known marker genes, GmIRT (for low Fe) and GmSULTR1;2b (for low S) (Qin et al, 2012 ; Ding et al, 2016 ), were also applied to confirm the Fe or S deficiency in this study (Figures S2D,E ). As shown in Figures 6 , 9 GmNRAMP genes were significantly down-regulated by Fe deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate potential roles for soybean NRAMP genes in nutrient homeostasis, GmNRAMPs were tested for alterations in expression in response to Fe or S deficiency. Two known marker genes, GmIRT (for low Fe) and GmSULTR1;2b (for low S) (Qin et al, 2012 ; Ding et al, 2016 ), were also applied to confirm the Fe or S deficiency in this study (Figures S2D,E ). As shown in Figures 6 , 9 GmNRAMP genes were significantly down-regulated by Fe deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…20. Previously, Ding et al (2016) identified 28 putative sulfate transporter (SULTR) genes in the soybean genome, including a member of the SULTR3 subfamily near the locus on chr. 20.…”
Section: Discussionmentioning
confidence: 99%
“…Among those dietary foods that have pharmacologically active metabolites, soybean ( Glycine max L.), which is commonly consumed in traditional Asian food, is a major source of oil and protein in the human and animal diet [4]. It is one of the natural substitutes for the treatment of a variety of hormone-dependent and independent disorders in humans [5].…”
Section: Introductionmentioning
confidence: 99%